Development of Hy-Quiz Learning Media Based on Android to Improve Studentsâ€™ Learning Motivation in Nomenclature of Hydrocarbon Derivative Compounds Sub Material - Nora, Nora; Lutfi, Achmad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This research aims to obtain a Hy-Quiz learning media based on Android as a learning media for nomenclature ofÂ Hydrocarbon Derivative Compounds sub material. The 4D development model is the method that has been used in this research. The instruments that have been used are validation sheet, studentsâ€™ response questionnaire sheet, student learning motivation questionnaire sheet, pretest, and posttest. The limited trial of this research was 27 students of SMA Negeri 3 Sidoarjo. The score of the validity test is more than three with good category. The score of practicality is more than three in every aspect with very practical category. The effectiveness of Hy-Quiz learning media is from studentsâ€™ learning outcomes and studentsâ€™ learning motivation questionnaire sheet. The classical completeness achieved is 82% and for the studentsâ€™ learning motivation get a response of â‰¥ 81% with a very effective category. So it can be concluded that the Hy-Quiz learning media has complied with the aspects of validity, practicality, and effectiveness as a learning media.